Synthesis of 1,3-Diols by O-Nucleophile Additions to Activated Alkenes - Gamba-Sánchez, Diego; Prunet, Joëlle (Synthesis, 2018)
The diastereoselective synthesis of 1,3-diols by addition of oxygen nucleophiles to activated alkenes is presented. This review focuses on homoallylic alcohol substrates that react with a relay compound to form an intermediate oxygen nucleophile, which in turn will lead to a protected 1,3-diol by intramolecular addition to the olefin moiety.1 Introduction2 Base Catalysis3 Organocatalysis4 Activation with Non-Metallic Electrophiles5 Activation with Transition Metal Derivatives6 Conclusions
Keywords: 1,3-diols; oxa-Michael; oxygen nucleophiles; activated alkenes; Tsuji–Trost reaction